Pengaruh Inflasi, Ekspor dan Impor Terhadap Stabilitas Nilai Tukar Rupiah per Dollar AS Periode 2016-2022 - Elsa Amitha Mutiara; Diana Puspitasari (Jurnal Simki Economic, 2024)
The stability of the rupiah exchange rate per US dollar continues to fluctuate, but in general the rupiah exchange rate per US dollar from 2016-2022 has depreciated. The depreciation of a currency will have a negative impact on the country's economy. The purpose of this study was to determine the effect of inflation, exports and imports on the stability of the rupiah exchange rate per US dollar for the period 2016-2022. This research uses a quantitative approach using secondary data with the data used in the form of panel data, namely a combination of time series and cross section data obtained through data published by Bank Indonesia and Badan Pusat Statistic for 7 years of observation from January 2016 to December 2022. The data analysis technique used to test the hypothesis is multiple linear regression analysis with data processing tools using SPSS. The results showed that Inflation has a negative but insignificant effect on the rupiah exchange rate per US dollar. Exports have a positive and significant effect on the rupiah exchange rate per US dollar. Imports have a positive and insignificant effect on the rupiah exchange rate per US dollar.